Water Quality Assessment of district Bagh(Tehsil Dhirkot) Azad Jammu and Kashmir using multivariate statistical methods - Madiha Madiha Kanwal (Sir Syed University Research Journal of Engineering and Technology)
The present study is conducted to identify the physical and chemical characteristics of District Bagh, Azad Jammu and Kashmir surface water. Fifteen locations were selected from study area to collect the water samples. The various physico-chemical parameters of water tested are pH,Temperature, Total dissolved solids (TDS), Sodium, Potassium, Sulphate, Nitrate, Calcium, Magnesium and Bicarbonates. The heavy metals including Cr, Cu, and Cl are also the part of our current research on the basis on the outcome of previous studies conducted in the urban areas of Azad Jammu and Kashmir. The final results concluded that bicarbonate was present in high concentration in all samples whereas the other parameters were in the compliance of prescribed World Health Organization standards. Furthermore, Cluster analysis and Principal Analysis were performed which shows similar results and effects of bicarbonates and hardness of water as major contributor of altering the concentration of other variables.